Compliance of Parenting Magazines Advertisements with American Academy of Pediatrics Recommendations - Michael B. Pitt; Jennifer N. Berger; Karen M. Sheehan (MDPI AG, 2016)
This study examined 3218 advertisements from the two parenting magazines with highest circulation in the United States. The authors compared each advertisement for a product for use by children, against all the published recommendations of the American Academy of Pediatrics (AAP) on topics such as toy safety, helmet use, age-defined choking hazards, infant sleep safety, and others. Any advertisement with images or products which went against a published AAP recommendation was deemed as non-adherence and was categorized according to the statement it contradicted. Nearly one in six (15.7%) of the advertisements contained example(s) of non-adherence to AAP recommendations, with twelve categories of offense represented. Categories ranked by overall share from most to least include: non-Food and Drug Administration (FDA) approved medical treatments, age-defined choking hazards, vitamins, cold medicine, formula, oral care, screen time, toy/playground safety, infant sleep, nutrition, water safety, and fall risk. Given that repeated exposure to messages in advertisements has been associated with changes in health decision-making, and parents often turn to parenting magazines for advice and ideas regarding their children, the publishers might consider screening the content in order to prevent confusing and potentially dangerous messages from being disseminated in the media.